2001
DOI: 10.1002/bit.1051
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of recombinant protein N‐glycan processing in NS0 and CHO cells

Abstract: Chinese hamster ovary and murine myeloma NS0 cells are currently favored host cell types for the production of therapeutic recombinant proteins. In this study, we compared N-glycan processing in GS-NS0 and GS-CHO cells producing the same model recombinant glycoprotein, tissue inhibitor of metalloproteinases 1. By manipulation of intracellular nucleotide-sugar content, we examined the feasibility of implementing metabolic control strategies aimed at reducing the occurrence of murine-specific glycan motifs on NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 72 publications
7
117
1
Order By: Relevance
“…However, this phenomenon is not universal for all cell lines, such as NS0 cells, which have been reported to have no positive feedback for glucosamine addition (Baker et al, 2001). It is noteworthy that since UDP-GlcNAc competes with CMPNeuAc for transport into the Golgi, elevated UDP-GlcNAc appears to cause a decline in sialylation (Rijcken et al, 1995).…”
Section: Glucosaminementioning
confidence: 96%
See 1 more Smart Citation
“…However, this phenomenon is not universal for all cell lines, such as NS0 cells, which have been reported to have no positive feedback for glucosamine addition (Baker et al, 2001). It is noteworthy that since UDP-GlcNAc competes with CMPNeuAc for transport into the Golgi, elevated UDP-GlcNAc appears to cause a decline in sialylation (Rijcken et al, 1995).…”
Section: Glucosaminementioning
confidence: 96%
“…UDP-GlcNAc is an important intracellular nucleotide sugar in late process of N-glycosylation pathway. Study found that adding glucosamine into the culture medium could elevate the intracellular UDPGlcNAc pool, especially added in conjunction with uridine (Baker et al, 2001). …”
Section: Glucosaminementioning
confidence: 99%
“…While improved sialylation of IFN-γ was the result of medium supplementation with the specific sialic acid precursor N-acetylmannosamine (ManNAc) at 20 mM in a CHO cell line (cotransfected with genes for dihydrofolate reductase) 134 , it remained unchanged for human tissue inhibitor of metalloproteinases 1 (TIMP-1) at the same ManNAc concentration in GS-NS0 and GS-CHO cells 135 . Likewise, feeding CHO-K1 cells producing EPO with 10 mM ManNAc increased sialylation 136 .…”
Section: Sialylationmentioning
confidence: 99%
“…The biochemical mechanisms of N-glycosylation in the endoplasmic reticulum (ER) and the Golgi apparatus are highly complex and involve many different processes, enzymes, substrates and cofactors 24 . Furthermore, the metabolism of the host cell is linked with the glycosylation pattern of the recombinant protein, and hence, metabolic control may come into play to influence N-glycan processing 106,123,135 . Metabolomic analysis of fed-batch cultures revealed increasing ornithine levels coincided with higher high mannose glycan levels 285 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most species predominantly have Nglycolyl-neuraminic acid (NGNA) rather than NANA. CHO cells have the advantage of the presence of a high percentage of NANA sialylation, but still include some NGNA sialylation (Baker et al 2001). …”
Section: Optimisation Of Glycosylation Patternsmentioning
confidence: 99%